Urgency OG Consitutional Amendement to Regulate Human Rights Protection in the Context of Digitalization - Karolus Charlaes Bego; Bambang Supriadi; Getah Ester Hayatulah; Arief Fahmi Lubis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The digital world's quick development has had a significant and wide-ranging effect on contemporary civilization. But this technical advancement also presents significant obstacles to the defense of human rights, especially in the areas of privacy, freedom of speech, and defense against cybercrimes. Despite the fact that Indonesia has a number of human rights laws, both domestic and international, the application of these laws in cyberspace frequently encounters difficulties. As a result, changing Indonesia's constitution is essential to guaranteeing the protection of people's fundamental rights online. The importance of revising Indonesia's constitution to protect human rights in the digital age is covered in this article, along with the opportunities and difficulties of putting these amendments into effect.